PENGEMBANGAN KEMAMPUAN DAN KEMANDIRIAN INDUSTRI PERTAHANAN INDONESIA (STUDI KERJASAMA PENGEMBANGAN DENGAN METODE PENTA-HELIX) - Novyan Aries Efendie; Geger Jaka Kiswara; Purboyo Purboyo (Journal of Industrial Engineering & Management Research, 2022)
Based on Law no. 16 of 2012 with the role of KKIP in developing the defense industry encourage domestic companies and other supporting elements to take part in building the ability and capacity to develop the defense industry, especially the production of equipment defense and security. The independence of a country's defense industry can ideally be analogized i.e. having the ability to be able to meet its own defense needs. In the concept of Penta-Helix involving 5 (five) elements including the government, the business world, academics/experts, the community and the media the masses to work together to build and develop the independence of the defense industry. Compared to development carried out only unilaterally, the results achieved are less optimal compared to the priority of the Penta-Helix method so that the independence of the defense industry is expected will be achieved in a better time and more optimal results. until now the role Indonesian domestic companies in the defense industry are still far from being expected in formulating real long term vision. The method used in this paper is descriptive analysis.